Beyond Apps: Digital Literacies in a Platform Society. (20th July 2020) - Nichols, T. Philip; LeBlanc, Robert Jean
Abstract: Young students must become proficient in the new literacies of 21st‐century technologies to be considered literate. This department explores how literacy educators can integrate information and communication technologies into the curriculum.